Deep Learning Approaches in Islamic Cultural History Learning at MTsN 2 Deli Serdang - Ahyun Widiya Ningsih; Mardianto Mardianto (Yayasan Vifada Cendikia Indonesia, 2026)
Purpose analyze the effectiveness of the deep learning approach in Islamic Cultural History (SKI) learning at MTsN 2 Deli Serdang, particularly in enhancing conceptual understanding, critical thinking skills, and students’ ability to relate historical materials to daily life. Research Design and Methodology: This research employed a qualitative case study approach involving one SKI teacher, one vice principal, and five ninth-grade students. Data were collected through classroom observations, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing with source triangulation Findings and Discussion: Showing the application of a deep learning approach through guiding questions, group discussions, presentations, and reflective activities increases student engagement and a deeper understanding of SKI material. Students are able to restate concepts in their own words, analyze the moral values of Islamic historical figures, and relate them to real-life contexts. However, its effectiveness is not uniform due to differences in motivation, individual character, and learning time limitations. Overall, the deep learning approach is effective in promoting meaningful and reflective SKI learning. Implications: This research is expected to provide both theoretical and practical benefits for the development of education